A definition for rapid weakening of North Atlantic and eastern North Pacific tropical cyclones. Issue 22 (27th November 2015) - Wood, Kimberly M.; Ritchie, Elizabeth A.
Abstract: Periods of 24 h over‐water weakening during 1982–2013 for North Atlantic (NAL) and eastern North Pacific (ENP) tropical cyclones (TCs) are examined to determine a threshold for rapid weakening (RW). These periods are defined by consistent weakening while the TC center remained more than 50 km from land. Weakening thresholds of 25, 30, and 35 kt represent the 87th (69th), 94th (80th), and 97th (89th) percentile in the NAL (ENP). Based on these statistics, the 30 kt threshold is chosen to define RW. Compared to all weakening periods, RW events are generally associated with greater 24 h official forecast errors, and these errors tend to be overestimates in both basins. These events usually occur as the TC crosses a sharp sea surface temperature gradient, encounters greater vertical wind shear, and entrains drier air. These metrics may be useful to forecasters assessing the likelihood of RW. Key Points: Rapid weakening is defined as a 30 kt decrease in intensity in 24 h Rapid weakening is more common in the eastern North Pacific than the North Atlantic Rapid weakening is associated with a combination of negative environmental factors